How well urban families are prepared for child birth and its complications - Chennakesavulu, Pujitha Vallivedu; Venkat, Cuddapah Gaurav; Siva Keerthana, Suddapalli; Govada, Harika; Preethi, Reddivari (International Journal Of Community Medicine And Public Health, 2020)
Background: Globally every day, approximately 830 women die from preventable causes related to pregnancy and childbirth. 99% of all maternal deaths occur in developing countries. Care before during and after childbirth can save the lives of women and new born babies which is also known as birth preparedness and complication readiness (BPACR). The objective of this study aims to assess practice of birth preparedness and complication readiness among families of women in the field practicing area of Kamineni Academy of Medical Sciences and Research Centre, Hyderabad. Methods: Field based descriptive study was done during August 2019 to February 2020 for a period of 6 months in urban field practising area. Sample size was 450 families, which includes, antenatal mothers 450 and their husbands 450, and 220 reproductive age group women. Results: Awareness of key danger signs during pregnancy (73.8%), labour/childbirth (56.7%) and postpartum (44%) were more among antenatal women whereas knowledge of danger signs of new born was highest among husbands of currently pregnant women. Planning of giving birth with a skilled provider was also high among antenatal women (98%) and in their husbands (97.5%), but saving for the same was very low in reproductive age group study population (20.4%). Conclusions: All these findings conclude Indian husbands of urban were more concerned about problems and safety of their offspring that is new born, than antenatal mother. Awareness of danger signs in the new born was lowest.